Pemetaan risiko yang sering terabaikan dalam industri perbankan syariah: Studi Literatur - Radliyah, Diana Rahmah (Maliki Interdisciplinary Journal, 2024)
The rapid development of Islamic banks has led to a deeper need to identify and manage overlooked risks in their operations. Through a comprehensive literature review, this article aims to shed light on critical risks that are often overlooked in the context of Islamic banks. Focusing the study on aspects of risk that are unique to the Islamic finance industry, this research provides valuable insights for practitioners and researchers in the field of Islamic banking risk management.